Pramipexole Enhances Levodopa's Therapeutic Efficacy in Parkinson’s Disease: role of glutaredoxin-1 (Grx1), peroxiredoxin-3 (Prx3), thioredoxin (Trx), 8-hydroxy-2′-deoxyguanosine (8-OHdG), and neurosteroid dehydroepiandrosterone sulfate (DHEA-S) - Shu, Yu; Qian, Jinjun (Journal of Medical Biochemistry, 2025)
Background: Parkinson's disease (PD) is characterized by progressive neurodegeneration and dopamine deficiency. Levodopa remains a cornerstone treatment, but its long-term use is associated with motor complications and reduced efficacy. This study investigates the clinical benefits of combining pramipexole with levodopa in PD patients, focusing on improvements in oxidative stress, cognitive function, and motor control. Additionally, the study explores the role of novel biomarkers, including glutaredoxin-1 (Grx1), peroxiredoxin-3 (Prx3), thioredoxin (Trx), 8-hydroxy-2′-deoxyguanosine (8-OHdG), and neurosteroid dehydroepiandrosterone sulfate (DHEA-S), in evaluating oxidative stress and neuroprotection.Methods: A total of 92 PD patients were enrolled and assigned to either a levodopa monotherapy group (n=46) or a pramipexole-levodopa combination group (n=46). Clinical efficacy was assessed using the Unified Parkinson's Disease Rating Scale (UPDRS). Cognitive function was evaluated using the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). Oxidative stress markers (SOD, GSH, GSH-PX, CAT, along with Grx1, Prx3, Trx, and 8-OHdG) were measured in serum samples. Additionally, DHEA-S was analyzed as a neurosteroid biomarker to assess its potential role in cognitive and motor function improvements. Quality of life (QOL) was assessed using the PDQ-39 questionnaire.Results: The combination therapy group exhibited a significantly higher effective rate (93.48%) compared to the levodopa group (78.26%) (P < 0.05). UPDRS scores were significantly lower in the combination group at 6 and 12 weeks post-treatment (P < 0.05). The combination group also showed a significantly lower incidence of adverse drug reactions (6.52% vs. 23.91%, P < 0.05). After 3 months, the combination group displayed significantly higher levels of SOD, GSH, GSH-PX, CAT, Grx1, Prx3, and Trx, while 8-OHdG levels were significantly reduced, indicating enhanced neuroprotection and reduced oxidative stress. DHEA-S levels were also elevated, correlating with improved MMSE and MoCA scores (P < 0.05), suggesting a neurosteroid-mediated cognitive benefit. QOL was significantly better in the combination group after 3 months of intervention (P < 0.05).Conclusions: Pramipexole combined with levodopa significantly improves clinical outcomes, reduces adverse effects, enhances cognitive function, and alleviates oxidative stress in PD patients. The inclusion of novel biomarkers such as Grx1, Prx3, Trx, 8-OHdG, and DHEA-S provides deeper insight into the molecular mechanisms underlying these therapeutic effects. This combination therapy represents a valuable strategy for improving PD management and warrants wider clinical application.
Keywords: Parkinson's disease; Levodopa; Pramipexole; Oxidative stress; Glutaredoxin-1; Peroxiredoxin-3; Thioredoxin, 8-OHdG; UPDRS; MMSE; MOCA; Cognition; Motor function; Neurosteroids